Quality of Duck Eggs (Anas domesticus Lin.) After 15 Days of Preservation Using Jackfruit Leaf Extract (Arthocarpus heterophyllus Lamk. - Azizah Mutmainah; Yusni Atifah (Jurnal Serambi Biologi, 2023)
Eggs are an important source of animal protein for humans apart from meat and fish. Duck eggs (Anas domesticus Lin.) are one type of egg that is widely consumed by Indonesians besides chicken eggs. As a livestock product, eggs have the disadvantage of being easily damaged, prone to egg crack and microorganisms easily contaminate resulting in a decrease in egg quality. To maintain the quality of eggs, preservation is carried out on eggs by utilizing natural ingredients, one of which is using jackfruit leaves. The purpose of this study was to determine the effect of jackfruit leaf extract and the length of egg soaking on the length of storage of duck eggs. This type of research is an experimental study using a completely randomized design (CRD) with 9 treatments and 3 repetitions. Data were analyzed using analysis of variance and continued with the DMRT test if there were significant differences. The results showed that soaking eggs with 45% jackfruit leaf extract for 36 hours effectively inhibited egg weight loss. Soaking eggs with 15% jackfruit leaf extract for 24 hours is effective for maintaining the yolk index and haught unit value, while inhibiting the increase in egg pH is effective at 15% soaking for 36 hours.